Instruction of myeloid cells by the tumor microenvironment: Open questions on the dynamics and plasticity of different tumor-associated myeloid cell populations - Schouppe, Elio; De Baetselier, Patrick; Van Ginderachter, Jo A.; Sarukhan, Adelaida (Oncoimmunology, 2012)
The versatility and plasticity of myeloid cell polarization/differentiation has turned out to be crucial in health and disease, and has become the subject of intense investigation during the last years. On one hand, myeloid cells provide a critical contribution to tissue homeostasis and repair. On the other hand, myeloid cells not only play an important role as first line defense against pathogens but also they are involved in a broad array of inflammation-related diseases such as cancer. Recent studies show that macrophages can exist in different activation states within the same tumor, underlining their plasticity and heterogeneity. In this review, we will discuss recent evidence on how the tumor microenvironment, as it evolves, shapes the recruitment, function, polarization and differentiation of the myeloid cell compartment, leading to the selection of myeloid cells with immunosuppressive and angiogenic functions that facilitate tumor progression and dissemination.